Lesson from rote’s palm tree to unlock the global harmony - Dewa Agung Gede Agung; Ulfatun Nafi’ah; Bayu Kurniawan (Cogent Arts & Humanities)
This study is of significant importance as it sheds light on the unique concept of harmony in the culture of Rote Island, Indonesia, and its potential for global application. The study, conducted between April and November 2021, revealed that Rote Island’s harmony concept offers notable advantages, such as cultural genuineness, durability, inclusiveness, and environmental consciousness. These findings are crucial for promoting global harmony while preserving local identities. The study’s framework, based on indigenous wisdom, provides essential insights for fostering unity on a larger scale, and the articulated policies emphasize the need for additional research and efforts to enhance understanding and practical implementation of this concept across diverse cultural settings. This research was conducted using a qualitative methodology between April and November 2021. The study employed interviews, observations, and documentation analysis to gain profound insights into the harmony concept of Rote Island. The study proposes that Rote Island’s notion of harmony can serve as a beneficial paradigm for promoting global harmony while preserving local identities. It emphasizes the need for additional research and efforts to enhance understanding and practical implementation of this concept across diverse cultural settings. The revised abstract incorporates the requested changes, including the importance of the work, key results, study time, framework, methods, and central policies.